Weighting faces according to Sheikh Muhammad Jawad Mughniyeh in the revealing interpretation (Journal of the College of Basic Education, 2022)
The research included the weightings adopted by Sheikh Muhammad Jawad Mughniyeh in choosing the correct meaning and the different connotations in wanting the required meaning, and the weighting faces are the indications that the interpreter uses in support of the appropriate meaning of the Qur’anic verse, so our interpreter used several indications and varied aspects of weighting with him, and the nature of the research required that I divide My research includes four topics, the first one includes weighting with Qur’an analogues, the second study weighting the apparent meaning of the Qur’an, the third study weighting by contextual significance, and the fourth topic is weighting in terms of general meaning